Petrology and SHRIMP zircon geochronology of granulites from Vesleknausen, Lützow-Holm Complex, East Antarctica: Neoarchean magmatism and Neoproterozoic high-grade metamorphism - Toshiaki Tsunogae; Daniel J. Dunkley; Kenji Horie; Takahiro Endo; Tomoharu Miyamoto; Mutsumi Kato (Geoscience Frontiers, 2014)
We report new petrological data and geochronological measurements of granulites from Vesleknausen in the highest-grade section of the Lützow-Holm Complex, part of the Gondwana-assembling collisional orogen in East Antarctica. The locality is dominated by felsic to intermediate orthogneiss (charnockite and minor biotite gneiss), mafic orthogneiss, and hornblende-pyroxene granulite, with deformed and undeformed dykes of metagranite and felsic pegmatite. Pseudosection analysis of charnockite in the system NCKFMASHTO, supported by geothermometry of mafic orthogneiss, was used to infer peak metamorphic temperatures of 750–850 °C, approximately 150 °C lower than those estimated for metasedimentary gneisses from Rundvågshetta, 6 km to the northeast. SHRIMP U-Pb analysis of zircons from feldspar-pyroxene gneiss, which corresponds to a partially molten patch around mafic orthogneiss, yielded a Concordia upper intercept ages of 2507.9 ± 7.4 Ma, corresponding to the time of formation of the magmatic protolith to the orthogneiss. Partial melting during peak metamorphism probably took place between 591 and 548 Ma, as recorded in rims overgrew around magmatic zircon. Our results suggest that Rundvågshetta-Vesleknausen-Strandnibba region in southwestern Lützow-Holm Bay, where orthogneisses are dominant, consists of a single crustal block, possibly formed by ca. 2.5 Ga arc magmatism. The Neoarchean magmatic terrane was tectonically mingled with other fragments (such as metasedimentary units in northern Lützow-Holm Bay) by subduction/collision events during the assembly of Gondwana supercontinent, and subsequently underwent ∼850 °C granulite-facies metamorphosed during Neoproterozoic to Cambrian final collisional event.